NEPENTHES CALCICOLA (NEPENTHACEAE), A NEW PITCHER PLANT FROM GULF PROVINCE, PAPUA NEW GUINEA - Gary W. Wilson; Stephanius Venter; Kapiro Q. Damas (REINWARDTIA, 2023)
A new species of pitcher plant from rain forest on limestone karst in the Purari River catchment in the Gulf Province of Papua New Guinea is described and illustrated as Nepenthes calcicola Gary W.Wilson, S.Venter & Damas. It is distinguished from N. neoguineensis on the basis of its distribution, ecology, habitat, and pitcher and inflorescence morphology. The new species is illustrated, and description is here given. The species is assessed as Vulnerable (VU) according to IUCN criteria.